Periplaneta americana Ameliorates Dextran Sulfate Sodium-Induced Ulcerative Colitis in Rats by Keap1/Nrf-2 Activation, Intestinal Barrier Function, and Gut Microbiota Regulation - Ma, Xuewei; Hu, Yichen; Li, Xin; Zheng, Xiaoting; Wang, Yitao; Zhang, Jinming; Fu, Chaomei; Geng, Funeng (Frontiers in Pharmacology, 2018)
Periplaneta americana, a magic medicinal insect being presence for over 300 million years, exhibits desirable therapeutic outcome for gastrointestinal ulcer treatment. Nowadays, P. americana ethanol extract (PAE) has been demonstrated to ameliorate ulcerative colitis (UC) by either single-use or combination with other therapeutic agents in clinics. However, its underlying mechanism is still seldom unknown. Herein, we investigated anti-UC activity of PAE by alleviating intestinal inflammation and regulating the disturbed gut microbiota structure in dextran sulfate sodium (DSS)-induced UC rats. Based on multiple constitute analyses by HPLC for quality control, PAE was administrated to dextran sulfate sodium-induced UC rats by oral gavage for two weeks. The anti-UC effect of PAE was evaluated by inflammatory cytokine production, immunohistochemical staining, and gut microbiota analysis via 16S rRNA sequencing. As a result, PAE remarkably attenuated DSS-induced UC in rats. The colonic inflammatory responses manifested as decreased colonic atrophy, intestinal histopathology scores and inflammatory cytokines. In addition, PAE improved intestinal barrier function via activating Keap1/Nrf-2 pathway and promoting the expressions of tight junction proteins. Mechanically, UC rats exhibited the disturbed gut microbial, i.e. the rising Firmicutes/Bacteroidetes ratio and the significantly reducing probiotics such as Lactobacillus, Roseburia and Pectobacterium, which were negatively correlated with these detected pro-inflammatory cytokines (secreted by immune CD4 + T cells, and including IFN-γ, TNF-α, IL-6, IL-8, IL-17, IL-1β). Besides, PAE administration regulated the abnormal intestinal microbial composition, which was similar to that in normal rats. Therefore, PAE could attenuate the DSS-induced UC in rats, by means of ameliorating intestinal inflammation, improving intestinal barrier function, and regulating the disturbed gut microbiota, in particular, it could improve beneficial intestinal flora growth, modulate the flora structure and restore the intestinal-immune system.